Enhancing Children's Critical Thinking Through Blended Problem-Based Learning and Eco-Literacy - Agustina, Ika; Harahap, Subur; Sukini, Sukini; Widodo, Hadi; Santosa, Tomi Apra; Safar, Muh; Ali, Makhrus (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of blended problem-based learning and eco-literacy on critical thinking skills in children. This type of research is a quantitative research with a meta-analysis approach. The inclusion criteria in the study are 1) the research must be relevant; 2) research comes from national or international journals indexed by SINTA and Scopus; 3) The research was published in the 2022-2025 time frame; 4) the research must be an experimental or quasi-experimental research; and 5) research obtained from the Google Scholar database; Mendeley, IEEE and ERIC. Data analysis with the JAMOVI application. The results of the study concluded that the 22 effect sizes analyzed had a significant influence of the blended problem-based learning and eco-literacy models on critical thinking skills in children with a value ( d = 0.991; z = 9, 343 ; p < 0.001) in the high effect size category.